Vaccination against Newcastle disease - Chulan, U.; Ibrahim, A.Latif; Mustaffa Babjee, A.; Sheikh-Omar, A.R. (Kluwer Academic Publishers-Human Sciences Press, 1982)
Two field trials carried out on 2,000 broiler chickens showed that chickens vaccinated with the lyophilised Newcastle disease (ND) "F" vaccine at 1, 21, and 42 days were protected when challenged at 14, 35, 56 and 70 days with the virulent strain of Newcastle disease virus (NDV) administered intramuscularly, intranasally, or by contact. A high percentage of the vaccinated birds were protected even though the haemaggglutination inhibition (HI) antibody levels were persistently low. Autopsies of the control and vaccinated birds that died from the challenge showed that most of the birds had lesions in the intestines.